Dwelling in resistance : living with alternative technologies in America - Schelly, Chelsea (Nature, Society, and Culture, 2017)
Most Americans take for granted much of what is materially involved in the daily rituals of dwelling. In Dwelling in Resistance, Chelsea Schelly examines four alternative U.S. communities-"The Farm," "Twin Oaks," "Dancing Rabbit," and "Earthships"-where electricity, water, heat, waste, food, and transportation practices differ markedly from those of the vast majority of Americans. Schelly portrays a wide range of residential living alternatives utilizing renewable, small-scale, de-centralized technologies. These technologies considerably change how individuals and communities interact with the material world, their natural environment, and one another. Using in depth interviews and compelling ethnographic observations, the book offers an insightful look at different communities' practices and principles and their successful endeavors in sustainability and self-sufficiency.